Bioactive Secondary Metabolites of Marine Fungi - Shin, Hee Jae (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue "Bioactive Secondary Metabolites of Marine Fungi" gathered ten publications, including two reviews and eight research articles, about marine fungi, ranging from the isolation and structure elucidation of new natural products to the biosynthetic pathways of marine fungal metabolites.